AI, Communication and Society: TAM Based Systematic Literature Review - Bayu Tresna Riyadi; Dedi Prasetia; Irwansyah Irwansyah (Journal Of Social Science (JoSS), 2026)
The rapid development of artificial intelligence (AI) has significantly transformed communication processes and social interaction in the digital era. AI technologies, such as chatbots, recommendation systems, and automated content generation, are increasingly integrated into various sectors, including education, healthcare, e-commerce, and public services. The Technology Acceptance Model (TAM) is widely used to explain technology adoption through key constructs such as perceived usefulness and perceived ease of use. This study aims to analyze research trends, contexts, and theoretical developments related to AI acceptance in communication using the TAM framework. The research employed a Systematic Literature Review (SLR) method. Articles were collected from the Scopus database using the keywords “Technology Acceptance Model,” “Artificial Intelligence,” and “Communication.” Based on the PRISMA screening and selection process, 32 relevant peer-reviewed journal articles published between 2018 and 2024 were included in the analysis. The findings show that quantitative approaches dominate AI acceptance studies, particularly those using survey methods and structural equation modeling. Research contexts are mainly concentrated in education and healthcare, while studies in journalism, social media communication, and organizational communication remain limited. The analysis also reveals that TAM is frequently combined with other theories, such as Diffusion of Innovations and Uses and Gratifications Theory, to better explain technology adoption. In conclusion, the Technology Acceptance Model remains a relevant framework for understanding AI adoption in communication contexts. However, future research should expand theoretical perspectives and methodological approaches while incorporating social values such as inclusivity, ethics, and sustainability within the Society 5.0 framework.